Effect of lie labelling on children's evaluation of selfish, polite, and altruistic lies. (9th January 2016) - Cheung, Him; Chan, Yawen; Tsui, Wan Chi Gigi
Abstract : This study investigates how 5‐ and 6‐year‐olds' evaluations of selfish, polite, and altruistic lies change as a result of whether these false statements are explicitly labelled as lies. We are also interested in how interpretive theory of mind may correlate with such evaluations with and without a lie label. Our results showed that labelling lowered children's evaluations for the polite and altruistic lies, but not for the selfish lies. Interpretive theory of mind correlated positively with the evaluation difference between the polite and altruistic lies and that between the selfish and altruistic lies in the label, but not in the non‐label condition. Correlation between the selfish and altruistic lies and that between the polite and altruistic lies were stronger with than without labelling, after controlling for age, and verbal and non‐verbal intelligence. We conclude that lie labelling biases children towards more negative evaluations for non‐selfish lies and makes them see lies of different motives as more similar. If a lie label is applied, whether lies of different motives are still evaluated differently depends on interpretive theory of mind, which reflects the child's ability to represent and allow different interpretations of an ambiguous reality.